2014
DOI: 10.11648/j.ijnfs.s.2014030601.11
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics of Garlic (Allium sativum L.) Oil: Effect of Extraction Procedure

Abstract: Garlic oil (GO) is behaves as a nutraceutical compound; however, its application is limited due to its pungency, undesirable aroma, low stability and solubility. The physicochemical properties of GO are certainly key parameters in the encapsulation process. Therefore, the aim of the current work was to study the effect of different extraction procedures such as solvent extraction, distillation method and supercritical fluid extraction (SCF) on the physicochemical properties of garlic oil. The yield of GO was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…These parameters can be ideal one to obtain the maximum yield at a commercial level. Thus, in the present study much higher oil yield was obtained compare to that reported by Ali Rafe et al 2014 [33] . They found that maximum yield were 5.5, 6 and 7% for steam distillation, solvent method and SCF-CO₂, respectively.…”
Section: Yield Of Garlic Oilsupporting
confidence: 47%
“…These parameters can be ideal one to obtain the maximum yield at a commercial level. Thus, in the present study much higher oil yield was obtained compare to that reported by Ali Rafe et al 2014 [33] . They found that maximum yield were 5.5, 6 and 7% for steam distillation, solvent method and SCF-CO₂, respectively.…”
Section: Yield Of Garlic Oilsupporting
confidence: 47%
“…As reported by Dehariya et al, garlic oil is rich in DADS (48.42%), allyl-methyl trisulfide (7.27%), trisulfide, di-2-propenyl (3.46%), and DAS (7.64%) [ 58 ]. Rafe et al studied the effect of the extraction procedure and solvent type on the physicochemical properties of garlic oil that can facilitate the encapsulation process [ 23 ]. The yield of garlic oil extraction expressed as the volume of oil after evaporation of the solvent was dependent on the extraction method used, with the highest result of 7.00% for supercritical fluid extraction (SCF).…”
Section: Methods Of Isolation Of Active Compoundsmentioning
confidence: 99%
“…The specific gravity of garlic oils, which is important for commercial feasibility, was also checked, but the method showed no effect on its value (0.894 g/cm 3 ). The higher efficiency achieved by SCF compared to solvent extraction and steam distillation may be related to better transport properties, such as diffusivity, mass transfer coefficient, and penetration capacity [ 23 ].…”
Section: Methods Of Isolation Of Active Compoundsmentioning
confidence: 99%
“…The experimental data (Supplementary Tables S1 , S2 , and S3 ) were subjected to analysis of variance (ANOVA) using ProcGLM and least significance difference (LSD) t -test programs of SAS version 9.2 [ 24 ] to investigate the statistical significance between different oil quality parameters. Differences between means were considered statistically significant at p < 0.05.…”
Section: Methodsmentioning
confidence: 99%